2020
DOI: 10.1680/jurdp.19.00018
|View full text |Cite
|
Sign up to set email alerts
|

A new typology of pocket parks: inspiring small spaces for changing cities

Abstract: The contemporary city has witnessed sweeping changes in terms of structure and image. New glittering globalised urban forms emerged, however, associated ‘anywhere’ contemporary urban spaces are often criticised as bland and meaningless. The global crisis of 2008 brought with it a heightened realisation of the need to manage cities differently and more sustainably. In recent decades, the concept of a public space/garden has changed from something largely ornamental and often to be viewed ‘passively’ to creating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…For example, a Danish study analyzed nine pocket parks in Copenhagen and identified healthrelated design elements, such as trails, historical features, seating, and flowerbeds to provide a basis for health-oriented pocket park design [52]. A study in Italy summarized the spatial configurations and elements of 13 types of pocket parks in Europe, from which the design principles for pocket parks were formulated [34]. The expert experience method is an empirical judgment method that relies on the knowledge and experience of experts to evaluate and select design schemes.…”
Section: Microscopic Landscape Design Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a Danish study analyzed nine pocket parks in Copenhagen and identified healthrelated design elements, such as trails, historical features, seating, and flowerbeds to provide a basis for health-oriented pocket park design [52]. A study in Italy summarized the spatial configurations and elements of 13 types of pocket parks in Europe, from which the design principles for pocket parks were formulated [34]. The expert experience method is an empirical judgment method that relies on the knowledge and experience of experts to evaluate and select design schemes.…”
Section: Microscopic Landscape Design Methodsmentioning
confidence: 99%
“…Author/source Definition 1967 American Society of Planning Officials [34] Where the need for outdoor space is greatest, small vacant lots and land occupied by derelict buildings can be acquired, usually at low cost, to be developed into small parks 1969…”
Section: Yearmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, pocket parks are built as evacuation sites in Japan, where earthquakes occur frequently ( Hu, 2016 , p. 1036). There are flood protection pocket parks that designed to promote some dual use spaces for protecting land from flooding ( Babalis, 2020 , 13). A pocket park in a campus called “Focus: HOPE” in Detroit provides users a pleasant place to enjoy the beauty of featured artwork (several murals and ornamentals painted by local artists displayed in the planning beds under the murals) and embrace the heritage of the local African American community ( Luks, 2001 , pp.97–100).…”
Section: Unique Contribution Of Pocket Parks In Helping To Fight the ...mentioning
confidence: 99%
“…Turning vacant lots or abandoned lots to pocket parks can be an effective strategy with lower turn-over costs than developing larger parks. In addition, the actual development of facilities of pocket parks may involve residents who use them, which keeps costs at a minimum while benefiting those residents in increasing community bonds ( Babalis, 2020 , p.4).…”
Section: Unique Contribution Of Pocket Parks In Helping To Fight the ...mentioning
confidence: 99%